Nationalism, terrorism, communalism : essays in modern Indian history - Heehs, Peter (Delhi : New York : Oxford University Press, 1998)
With special reference to Bengal; articles.
1. Introduction: Terrorism and the National Movement -- 2. The Maniktala Secret Society: An Early Bengali Terrorist Group -- 3. Aurobindo Ghose and Revolutionary Terrorism -- 4. Foreign Influences on Bengali Revolutionary Terrorism -- 5. Bengali Religious Nationalism and Communalism -- 6. Indian Communalism: A Survey of Historical and Social-Scientific Approaches -- 7. Appendix: Myth, History and Theory.
Includes bibliographical references and index.
Keywords: Nationalism -- India -- Bengal; Terrorism -- India -- Bengal; Communalism -- India -- Bengal; Bengal (India) -- Politics and government -- 20th century